HPV vaccine-related articles shared on Facebook from 2019 to 2021: Did COVID make a difference? - L. Aubree Shay; Ashley McKenzie; Elaine Avshman; Lara S. Savas; Ross Shegog (Elsevier, 2024)
Objective: HPV vaccination is recommended for children beginning at age 9 to prevent several types of cancer. Many parents turn to Facebook for health information. This study describes changes in HPV vaccine-related articles shared on Facebook amidst the COVID-19 pandemic. Methods: HPV-related articles shared on Facebook (2019-2021) were collected using Buzzsumo, a social media analytics tool and analyzed using content analysis. Articles were categorized by valence, misinformation, evidence types, persuasive tactics, and framing. We quantified these data and tested for difference by article year. Results: Of the 138 included articles, 51% had positive valence towards the vaccine and 36% had negative valence. In 2021, there was a significant increase in positive messaging (72% vs. 44% in 2019/2020; p < 0.01) and misinformation decreased from 50% in 2019 to 24% in 2021 (p = 0.04). Persuasive strategies were more common in 2019 than in later years. Conclusion: Despite decreased engagement in 2021, more positive HPV vaccine messaging was observed, although a quarter of articles still contained misinformation. Our results can inform strategies for communicating with parents about the HPV vaccine. Innovation: Our study is the first to analyze HPV-related articles linked on Facebook and to assess for differences during the pandemic.